Enzymatic Cascade Synthesis Provides Novel Linear Human Milk Oligosaccharides as Reference Standards for xCGE‐LIF Based High‐Throughput Analysis. Issue 3 (23rd August 2018) - Fischöder, Thomas; Cajic, Samanta; Reichl, Udo; Rapp, Erdmann; Elling, Lothar
Abstract : A rising amount of known health benefits leads to an increased attention of science and nutrient industry to human milk oligosaccharides (HMOS). The unique diversity of HMOS includes several rare, complex, and high molecular weight structures. Therefore, identification and elucidation of complex structures, which may occur only in traces, poses a daunting analytical challenge, further complicated by the limited access to suitable standards. Regarding this, inherent diversity of HMOS and their structural complexity make them difficult to synthesize. The use of recombinant Leloir ‐glycosyltransferases offers a common strategy to overcome the latter issues. In this study, linear long‐chained Lacto‐ N ‐biose‐type (LNT) and Lacto‐ N ‐neo‐type (LNnT) HMOS are tailored far beyond the known naturally occurring length. Thereby novel well‐defined reference standards for screening HMOS composition by high performance and high throughput analytics are provided. It is shown here for the first time the synthesis of LNT oligomers up to 26 and LNnT oligomers up to 30 sugar units in a semi‐sequential one‐pot synthesis as analyzed by high performance multiplexed capillary gel electrophoresis with laser‐induced fluorescence detection (xCGE‐LIF). While being a high‐throughput method, xCGE‐LIF can also handle long chained linkage isomers of challenging similarity, some of them even present only in trace amounts. Abstract : The unique diversity of human milk oligosaccharides (HMOS) poses a daunting analytical challenge for identification and elucidation of their composition, further complicated by the limited access to suitable standards. This study demonstrates the enzymatic synthesis of linear long‐chained HMOS as novel reference standards for analysis by high performance multiplexed capillary gel electrophoresis with laser‐induced fluorescence detection (xCGE‐LIF).